2013
DOI: 10.2478/botcro-2013-0002
|View full text |Cite
|
Sign up to set email alerts
|

Novel polymorphic microsatellite markers from turmeric, Curcuma longa L. (Zingiberaceae)

Abstract: -Twenty one polymorphic microsatellite loci were isolated and characterized from turmeric (Curcuma longa L.). These markers were screened across thirty accessions. The number of alleles observed for each locus ranged from two to eight with an average of 4.7 alleles per locus. The discrimination power of these markers ranged from 0.25 to 0.67 (average 0.6). The simple sequence repeat (SSR) markers can complement the currently available SSR markers and would be useful for the genetic analysis of turmeric accessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 13 publications
(13 reference statements)
1
9
0
1
Order By: Relevance
“…Amplification of multiple bands through SSR marker in the present study could be due to the alloployploidy nature of turmeric (Ravindran et al 2007), where the basic chromosome number is suggested as x = 21, in turn which was originated by dibasic amphidiploidy from x = 9 and x = 12 or by secondary polyploidy (Nair et al 2010;Leong-Skorhickova et al 2007). Multiple bands produced by SSRs in this study is in agreement with other reports of turmeric (Siju et al 2010;Senan et al 2013;Singh et al 2015) and other polyploid species such as potato (Rocha et al 2010) and apple (Liu et al 2014) including allopolyploid species such as wheat (Nicot et al 2004;Sehgal et al 2012).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Amplification of multiple bands through SSR marker in the present study could be due to the alloployploidy nature of turmeric (Ravindran et al 2007), where the basic chromosome number is suggested as x = 21, in turn which was originated by dibasic amphidiploidy from x = 9 and x = 12 or by secondary polyploidy (Nair et al 2010;Leong-Skorhickova et al 2007). Multiple bands produced by SSRs in this study is in agreement with other reports of turmeric (Siju et al 2010;Senan et al 2013;Singh et al 2015) and other polyploid species such as potato (Rocha et al 2010) and apple (Liu et al 2014) including allopolyploid species such as wheat (Nicot et al 2004;Sehgal et al 2012).…”
Section: Discussionsupporting
confidence: 91%
“…It possesses several activities such as anti-inflammatory, anti-oxidant, antimicrobial, antiviral, antifungal, insecticidal, nematocidal activity, anti-ageing, lipid lowering effects, antiallergic, immunomodulatory, antidiabetic, and anticancerous properties (Sasikumar 2005;Corcolon et al 2015). Turmeric is predominantly vegetatively propagated and has been reported as triploid (2n = 3x = 63; x = 21) and nonaploid (2n = 9x = 63; x = 7) (Senan et al 2013). Cultivars of turmeric are highly diversified and its taxonomy is quite confusing.…”
Section: Introductionmentioning
confidence: 99%
“…During the span of experimentation, only 17 EST-SSR and 35 genomic SSR markers had been reported in turmeric. This limited availability arose the need to expand the then existing repertoire of microsatellite markers for future studies aiming at better estimation of genetic variability for the effective conservation of the genetic resources of turmeric (Senan et al 2013). SSR markers were utilized in the present study due to the fact that they are highly reproducible, abundantly distributed in eukryotic genomes, highly stringent and hypervariable.…”
Section: Resultsmentioning
confidence: 99%
“…Assessment of genetic diversity using ISSR and RAPD markers were carried out among C.longa and other 14 species of curcuma and placed them into seven groups which are congruent with the morphological characters-based classification (Syamkumar and Sasikumar 2007). Recent progress in molecular markers was the development and characterization of EST-derived and genomic microsatellites which can be used for the diversity analysis of turmeric (Joshi et al 2010;Senan et al 2013).…”
Section: Biotechnological Aspects Of Turmericmentioning
confidence: 98%